Improving Body Mass Index of School-Aged Children Using a Nine-Week Rope Skipping Training Intervention: A One-Group Pre-Test Post-Test Design - James Boadu Frimpong; Michael Agyei; Daniel Apaak; Edward Wilson Ansah; Larissa True (MDPI AG, 2022)
Studies examining the effectiveness of rope skipping training to improve the body mass index (BMI) of school children are scarce. Hence, this study examined the effectiveness of nine-week skipping training on the BMI of primary six school-aged children (n = 77). The participants underwent 30 min of skipping training three days per week over a nine-week period. The participants' BMI was measured at the baseline and during weeks 3, 6 and 9. The results from a one-way ANOVA with repeated measures indicated a statistically significant difference in the BMI for both males [F(3,111) = 9.42, p < 0.001, ηp2 = 0.203] and females [F(3,114) = 7.35, p < 0.001, ηp2 = 0.162], suggesting an improvement in BMI. Post hoc comparisons with a Bonferroni adjustment revealed significant differences in BMI after nine weeks of intervention for males between the pre-test (M = 21.47, SD = 4.94) and the 9-week post-test (M = 20.15, SD = 4.36), and for females between the pre-test (M = 21.56, SD = 5.80) and the 9-week post-test (M = 20.68, SD = 5.32). This study demonstrated that regular participation in vigorous physical activity such as skipping training could promote child health by preventing the likelihood of young children being overweight. This result has implications for the inclusion of skipping training into the school life of school-aged children to help manage their BMI levels.